2005
DOI: 10.1042/bj20050538
|View full text |Cite
|
Sign up to set email alerts
|

The hnRNPs F and H2 bind to similar sequences to influence gene expression

Abstract: The hnRNPs (heterogeneous nuclear ribonucleoproteins) F and H2 share a similar protein structure. Both have been implicated as regulating polyadenylation, but hnRNP H2 had a positive effect, whereas hnRNP F acted negatively. We therefore carried out side-by-side comparisons of their RNA-binding and in vivo actions. The binding of the CstF2 (64 kDa cleavage stimulatory factor) to SV40 (simian virus 40) late pre-mRNA substrates containing a downstream GRS (guanine-rich sequence) was reduced by hnRNP F, but not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 37 publications
4
64
0
Order By: Relevance
“…93 Our results indicate that mTOR stimulates the recruitment of some hnRNP isoforms to the 5' mRNA cap, 72 which may provide a regulated mechanism for the selective recruitment of mRNAs to the translational machinery. Consistent with this possibility, is the fact that hnRNP A1 and F have been shown to regulate the translation of specific mRNAs 95,96 ; however, the involvement of mTOR in this process is currently unknown.…”
Section: Mtorc1 Regulates the Cap Recruitment Of A Network Of Translamentioning
confidence: 93%
“…93 Our results indicate that mTOR stimulates the recruitment of some hnRNP isoforms to the 5' mRNA cap, 72 which may provide a regulated mechanism for the selective recruitment of mRNAs to the translational machinery. Consistent with this possibility, is the fact that hnRNP A1 and F have been shown to regulate the translation of specific mRNAs 95,96 ; however, the involvement of mTOR in this process is currently unknown.…”
Section: Mtorc1 Regulates the Cap Recruitment Of A Network Of Translamentioning
confidence: 93%
“…These proteins possess a modular and highly conserved structure encompassing two glycine-rich auxiliary domains and two or three repeats of RNA binding quasi-RNA recognition motif (qRRM). The hnRNP H/F members regulate both inhibitory and stimulatory alternative splicing of target genes through binding cognate Grich intronic and exonic sequences in proximity to the polyadenylation sites (13).…”
Section: Introductionmentioning
confidence: 99%
“…While hnRNP F might be expected to block any poly(A) site based on its sequence preference for downstream regions (Alkan, Martincic et al 2006), we found by a micro-array analyses of hnRNP F transfected cells that only some genes were affected, most notable among these were secretory Igh and ELL2, a transcription elongation factor (Martincic, Alkan et al 2009). The finding that there are U1A binding sites up-stream of the Igh mu secretory poly(A) site indicates a selectivity consistent with the observed increased use of the site when U1A levels fall (Phillips and Virtanen 1997).…”
Section: Alterations In Trans-acting Factors For Polyadenylation In Bmentioning
confidence: 74%
“…A shift in the SR-proteins is seen from the activating type (ASF/SF2) in B-cells to the repression type (SRp20) in plasma cells. The factors hnRNP F and U1A, both of which block the secretory-specific poly(A) site from functioning, are reduced in plasma cells (Veraldi, Arhin et al 2001;Milcarek, Martincic et al 2003;Alkan, Martincic et al 2006) and (Ma, Gunderson et al 2006) which would allow the secretory site to function better. The major effectors in the alternative processing in B versus plasma cells are summarized in Table 1.…”
Section: Differential Expression Of Factors In a Number Of Pathways Smentioning
confidence: 99%